Association of the Affordable Care Act Medicaid expansion and receipt of palliative care among individuals newly diagnosed with advanced stage cancers. Issue 28 (1st October 2022) - Han, Xuesong; Shi, Kewei; Zhao, Jingxuan; Nogueira, Leticia M; Parikh, Ravi Bharat; Jemal, Ahmedin; Yabroff, K. Robin Robin
Abstract : 73 Background: Receipt of palliative care is a guideline-based practice but is low among patients with advanced cancer is low in the U.S. Lack of insurance is a major barrier to accessing palliative care. It is unknown, however, whether Medicaid expansion under the Affordable Care Act (ACA) and the associated increase in insurance coverage among individuals diagnosed with cancer has led to increased palliative care. We use a nationwide dataset to examine the association between Medicaid expansion and receipt of palliative care among individuals newly diagnosed with advanced stage cancers. Methods: Individuals aged 18-64 years with newly diagnosed stage-IV solid cancers pre- (2010-2013) and post- (2014-2019) ACA Medicaid expansion were identified from the National Cancer Database. We used difference-in-differences (DD) analyses to estimate the association between Medicaid expansion and changes in receipt of palliative care as part of first-line therapy, adjusting for age group, sex, race/ethnicity, area-level poverty, metropolitan status, comorbidity, facility type, palliative care specialist availability, diagnosis year and state of residence. Stratified analyses were conducted by cancer type and sociodemographic factors. Results: A total of 685, 781 individuals diagnosed with stage IV cancers were included from Medicaid expansion (N = 439, 142) and non-expansion (N = 246, 639) states. The percentage of eligible patients who received palliative care as part of first-line therapy increased from 17.0% pre-ACA to 18.9% post-ACA in Medicaid expansion states and from 15.7% to 16.7% in non-expansion states, resulting in a net increase (DD) of 1.4 (95%CI = 1.0-1.8) percentage points in expansion states after adjusting for sociodemographic and clinical factors. The increase in receipt of palliative care in expansion states compared to non-expansion states was greater for patients with advanced pancreatic (DD = 2.5; 95%CI = 0.8-4.3), colorectal (DD = 2.2; 95%CI = 1.1-3.3), female breast (DD = 1.9; 95%CI = 0.1-3.7), lung (DD = 1.6; 95%CI = 0.7-2.5), oral cavity and pharynx (DD = 1.1;95%CI = 0.5-1.6) cancers, and non-Hodgkin lymphoma (DD = 0.9; 95%CI = 0.2-1.5). The improvement in receipt of palliative care was larger among individuals aged 55-64 years, non-Hispanic White patients, and patients residing in middle-income areas and nonmetropolitan areas. Conclusions: Among individuals newly diagnosed with stage-IV cancer, Medicaid expansion was associated with increases in receipt of palliative care, although overall use was low. Furthermore, the increase varied by cancer type and sociodemographic factors. Improving access to insurance can facilitate access to guideline-based palliative care.